2019
DOI: 10.1002/2211-5463.12740
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum quality control of LDLR variants associated with familial hypercholesterolemia

Abstract: Loss‐of‐function mutations in the low‐density lipoprotein receptor (LDLR) gene can cause familial hypercholesterolemia (FH), but detailed functional evidence for pathogenicity is limited to a few reported mutations. Here, we investigated the cellular pathogenic mechanisms of three mutations in LDLR causing FH, which are structurally identical to pathogenic mutations in the very low‐density lipoprotein receptor (VLDLR). Similar to the VLDLR mutants, LDLR mutants D482H and C667F were found to be localized to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 38 publications
1
35
1
Order By: Relevance
“…Other chaperones GRP94, ERP72 (PDIA4), and CNX have also been found to associate with class II mutants (G544V) but not with wild type LDLR ( Sørensen et al, 2006 ). Recently we have also reported that three LDLR class II variants were found to be associated with ER chaperones: GRP78 (BiP), GRP94, the lectin chaperone CNX ( Kizhakkedath et al, 2019 ). In cells overexpressing the G544V mutant, the ER-retention of the mutant was shown to induce ER-stress and activation of UPR as evidenced by the upregulation of mRNAs for GRP78, GRP94, ERP72, attributed to the activity of ER sensors IRE1 and PERK ( Sørensen et al, 2006 ).…”
Section: Erad Processing Of Ldlr Mutantsmentioning
confidence: 96%
See 4 more Smart Citations
“…Other chaperones GRP94, ERP72 (PDIA4), and CNX have also been found to associate with class II mutants (G544V) but not with wild type LDLR ( Sørensen et al, 2006 ). Recently we have also reported that three LDLR class II variants were found to be associated with ER chaperones: GRP78 (BiP), GRP94, the lectin chaperone CNX ( Kizhakkedath et al, 2019 ). In cells overexpressing the G544V mutant, the ER-retention of the mutant was shown to induce ER-stress and activation of UPR as evidenced by the upregulation of mRNAs for GRP78, GRP94, ERP72, attributed to the activity of ER sensors IRE1 and PERK ( Sørensen et al, 2006 ).…”
Section: Erad Processing Of Ldlr Mutantsmentioning
confidence: 96%
“…Many membrane and secretory proteins that fail to conform to the ER quality control (ERQC) are dislocated into the cytosol and degraded by the proteasome by a process termed as ER-associated degradation (ERAD) ( Vembar and Brodsky, 2008 ; Ruggiano et al, 2014 ; Sun and Brodsky, 2019 ). Misfolded proteins can still retain their function and premature ERAD of mutant misfolded proteins is accounted for the cellular pathogenesis of several congenital disorders ( Ward et al, 1995 ; Hume et al, 2009 ; Ali et al, 2011 ; Al-Kindi et al, 2014 ; Kizhakkedath et al, 2014 , 2019 ; John et al, 2015 ). Sometimes the quality control mechanisms fail to recognize folding-incompetent forms which leads to the accumulation of folding-intermediates in the ER, causing ER stress.…”
Section: Mechanisms Of Protein Quality Control and Proteostasis Regulmentioning
confidence: 99%
See 3 more Smart Citations